APRIORI ALGORITHM FOR IMPLEMENTATION OF RAW MATERIAL PURCHASE DATA ANALYSIS IN PT MAHAKAM BETA FARMA - Dewi Risdawati; Nita Merlina (LPPM Nusa Mandiri, 2020)
PT Mahakam Beta Farma is a manufacturing company in the pharmaceutical field and there are obstacles in the storage of raw materials so that the process of entering and exiting raw materials is not effective. The solution to this problem is to rearrange the location of raw materials in the warehouse to facilitate the distribution of raw materials when entering or leaving so that when needed for the production process does not require much time in the search, which will also have an impact on the smooth production process. The basis for determining the layout of raw materials in the warehouse is to analyze what raw materials are often purchased at the same time for 1 year with data mining using apriori algorithm method. The application used to process the purchase of raw material that is large enough is Tanagra 1.4. The results of this study obtained 12 patterns of purchase of raw materials with a minimum value of 80% support, 90% minimum confidence, and lift ratio o as materials to recommend the re-layout of raw materials in the warehouse.